PENGHILANGAN GEN Lacz DARI PLASMID pUKC 815 UNTUK MEMBENTUK VEKTOR EKSPRESI DI RAGI Saccharomyces cereviceae - Ahmad Thontowi; Ni Nyoman T P; Mariatun Loegito (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
The pUKC 815 plasmid was a shuttle vector. This plasmid had the genetic marker to the urasil (URA3) in yeast and ampicillin resistanced marked in E. coli. The pUKC 815 plasmid also had a promotor gene PGK. The PGK promotor was expected to inducting the expression of amylase gene. Expression of amylase gene in S. cereviceaecould be do by preparing the pUKC 815 plasmid as an expression vector through reducing the LacZ gene then it would be replace by the amylase gene. This research used several methods. These method were isolate the pUKC 815 plasmid, the digestion of the pUKC 815 DNAwith the BamHI restriction enzyme, electrolution, ligation and the transformation of 8.000 pb fragment pUKC 815 plasmid in to the cell of E. coli DH5a. the result shown that the expression vector in yeast (S. cereviceae) from the pUKC 815 plasmid with the 8.000 pb was formed.